Adjusting to New Realities : MENA, The Uruguay Round, and the EU-Mediterranean Initiative - Fennell, Susan (IMF Working Papers; Working Paper, 1997)
This paper addresses concerns that the Middle East and North Africa (MENA) region, with the exception of the GCC economies, has lagged behind in trade liberalization. This delay has adversely affected production efficiency and consumer welfare and could reduce the region's ability to attract foreign investment. Against this background, the paper examines the major challenges facing MENA if it is to benefit from the opportunities presented by the Uruguay Round and the European Union Mediterranean Initiative. It concludes with an overview of measures that MENA countries will need to implement to benefit from these trade-enhancing initiatives.